Bangkit Dari Krisis: Dinamika Motivasi Kerja dalam Membangun Resiliensi Pekerja Pariwisata di Kawasan Wisata Ubud Pasca Krisis Pandemi - I Putu Andre Adi Putra Pratama; Putu Ade Wijana; Isvari Ayu Pitanatri; Ni Putu Lilik Widyayanthi (TOBA: Journal of Tourism, Hospitality, and Destination, 2026)
The COVID-19 pandemic crisis has historically exerted extreme economic pressure on tourism workers in Ubud, particularly within the highly vulnerable non-star accommodation sector. This study aims to explore and analyze the dynamics of work motivation as a core element shaping post-pandemic tourism worker resilience, utilizing the conceptual framework of ERG (Existence, Relatedness, Growth) Theory. This research applies a qualitative method with a phenomenological approach, gathering data through in-depth interviews with employees and business owners in the guest house, homestay, villa, and bungalow sectors. The findings reveal an intriguing paradox: the severe threat to Existence Needs, caused by the sudden loss of income, actively reawakened a survival instinct that triggered strong work perseverance and adaptive flexibility. Furthermore, the workers' emotional stability was maintained through the fulfillment of Relatedness Needs, which are deeply rooted in the local cultural wisdom of “Menyama Braya” (brotherhood/kinship). This cultural concept created a psychological safety net and fostered profound worker loyalty despite the complete absence of financial incentives. Moreover, the crisis situation significantly stimulated Growth Needs, driving workers to adapt through role expansion (multitasking), the acquisition of new skills, and the adoption of digitalization. In conclusion, the resilience of tourism workers in Ubud is not merely a passive capacity to endure, but an active motivational transformation and a strategic effort in role renegotiation and competency enhancement amidst profound uncertainty.